2013
DOI: 10.1017/s1368980013000931
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iodine-deficiency disorders on academic achievement of schoolchildren in Southern Ethiopia

Abstract: Objective: The present study aimed to assess the effect of iodine deficiency on academic achievement of schoolchildren in Wolaita Sodo town, Southern Ethiopia. Design: School-based comparative cross-sectional study. Settings: Primary school in Sodo town, Southern Ethiopia. Subjects: A sample population of 270 children with goitre and 264 without goitre. All students in each class were examined for the presence of goitre and classified based on WHO recommendations. Results: Among children with goitre, a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(21 reference statements)
3
9
0
Order By: Relevance
“…Accordingly, the higher odds of having goiter were noted among children from households using the unprotected source of water. The finding was in agreement with the previous studies of other developing countries [10, 4345], in which contamination of drinking water with Coliforms and E. Coli contributes to the development of goiter. The current study revealed that the majority, (96.6%), of the households did not treat water to make it safer for consumption.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, the higher odds of having goiter were noted among children from households using the unprotected source of water. The finding was in agreement with the previous studies of other developing countries [10, 4345], in which contamination of drinking water with Coliforms and E. Coli contributes to the development of goiter. The current study revealed that the majority, (96.6%), of the households did not treat water to make it safer for consumption.…”
Section: Discussionsupporting
confidence: 93%
“…The previous studies noted that iodine-deficient children perform poorly in school, suffered from the higher incidence of learning disabilities and lower intelligent quotient (IQ) [5, 10]. Besides to this, ID negatively affects working capacity, quality of life and economic productivity of the community at large [11].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed a highly significant correlation (r = 0.39, p = 0.001) between goiter and short-term memory among the children studied, but no significant differences were detected in other cognitive tests between children with goiter and without goiter. In line with this, a study by Wolka et al from 2014 observed that children with goiter were 1.8 times more likely to have low academic achievement than those who did not have goiter (adjusted OR = 1.8; 95 % CI 1.2, 2.5) [27]. Moreover, goiter was associated with both absenteeism and a higher prevalence of below-average academic scores (57.0 % of children with goiter were below average vs. 41.3 % without goiter, p < 0.01).…”
Section: [ 22-28]mentioning
confidence: 66%
“…Only few areas of Jimma zone [7,11,18], Arsi zone [19], Bale zone [20] and Haramaya district [21] were covered, while other zones and districts have no information. Southern Nation Nationalities and Peoples were targeted with three independent studies of zones and districts such as Gamo Gofa [19], Kafa [22], Sidama [23][24][25], Hawasa [26] and Sodo [27,28]. Four reports on the Amhara region targeted areas in Shoa zone [19], Bahir Dar town [29], Wombera and Burie districts [30], and Lay Armachiho district [31].…”
Section: Regional Studies Of Id In Ethiopia Are Incompletementioning
confidence: 99%
“…Vitamin A deficiency among children is associated with increased risks of blindness, xeropththalmia, diarrhea, measles, respiratory infections, and mortality . Iodine deficiency negatively affects mental development and intelligence quotient of children under five as well as academic achievements of school‐aged children …”
Section: Child Micronutrient Statusmentioning
confidence: 99%